Personal Names in the Hebrew Bible with Second-Millennium B.C. Antecedents - Hess, Richard S. (Bulletin for biblical research, 2015)
Recent studies in the phonemic representations of ancient Near Eastern languages in cuneiform and Hebrew, as well as the growing inventory of these names, have resulted in the need to revisit claims for and against the presence of personal names and name elements of the second millennium B.C. as thought to occur in Biblical Hebrew sources. Using the non-Israelite personal names in the biblical book book of Joshua as a test case, I will argue that some names previously thought to be attested no later than the second millennium now can be found in first-millennium sources as well. On the other hand, new evidence will also confirm that several personal names remain unattested in later sources but demonstrate more widespread appearance in the second-millennium B.C. sources than earlier evidence had formerly suggested. This study will make use of recent publications of Hurrian and Anatolian texts and names, as well as research on the phonemic representation of these languages in a West Semitic script such as Hebrew, which is not commonly used for the language. Conclusions regarding names and their sources provide important evidence (1) for dating onomastic sources in the earliest traditions that may lie behind the biblical text, and (2) for evidence of the presence of north Syrian cultural influence in the southern Levant during the Early Iron Age.